Internalisasi Nilai-Nilai Pendidikan Islam Pada Anak Usia Dini: Pondasi Pembentukan Karakter Sejak Dini - Kalbi Jafar; Maswati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the internalization of Islamic education values in early childhood as the foundation for character development from an early age. Using a descriptive qualitative approach, the study explores habituation strategies and teacher role modeling, as well as the collaborative role of parents and the school environment in consistently instilling Islamic values. The results show that value habituation through daily routines and teacher role modeling are key factors in shaping the Islamic character of children. Additionally, collaboration between schools and parents strengthens the internalization process, enabling children to naturally and sustainably practice Islamic values. These findings highlight the importance of synergy between educators and families in supporting the moral development of early childhood. The study recommends that Islamic education for early childhood implement consistent habituation methods and enhance communication with parents to create a holistic and effective character education.